Challenges and opportunities in implementing video-based extension approaches targeting women farmers: An implementer’s perspective - Rwamigisa, Patience B.; Namyenya, Angella; Butele, Cosmas Alfred; Shah, Mansi; Githuku, Fridah; Njung’e, Dennis (International Food Policy Research Institute, 2023)
Agricultural extension services play an important role in agricultural development. Timely and reliable information services are key to improving farmers’ knowledge of strategies to increase agricultural productivity, assisting them in accessing inputs and credit, providing early warning against pests and other shocks, and offering them critical advice on climate action. However, equitable access to knowledge, information, and technology remains challeng ing in most countries. This inequity is even more pronounced among farmers from marginalized groups, including women farmers, resulting in their limited access to climate resilience-enhancing technologies and practices. This note summarizes findings from implementers of participatory video-based extension interventions in India, Kenya, and Uganda. The findings suggest that videos targeting women farmers can reach them effectively. Still, participa tory video-based extension should be accompanied by group discussions, providing complementary inputs, and dismantling other barriers that impede women’s agency and achievements in agriculture.